ҚАРАҚАЛПАҚСТАН САЛЫГЕРШИЛИК ИЛИМИ ТАРИЙХЫНАН - Қайпназаров, А.Ш. (SCIENCE and SOCIETY, 2018)
In the article there is the information about forming of scientific-research institutions in the field of rice-growing after establishing conditions for the development of rice planting in our region.
Keywords: иқтисодиёт; режа; динамика; ривожланиш; қишлоқ хўжалиги; иқтисодий сектор; соҳа